PENGARUH TANAMAN RUMPUT BEBEK (Lemna minor) TERHADAP PENURUNAN BOD DAN COD LIMBAH CAIR DOMESTIK - Endro, Sutrisno; Sri, Sumiyati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2010)
Domestic wastewater coming from household activities is an environmental problem that needs to be taken  seriously.  For  it.  appropriate  alternative  treatment  is  needed,  both  in  terms  of  economic efficiency and the environment. As one attempts to solve is to take advantage of duckweed plants as a medium  to  improve  the  quality  of  the  leachate  is  biologically  or  as  bioakumulator  substance  - contaminants. This study aims to determine the effectiveness (efficiency) of duckweed plants (Lemna minor) in a decreasing concentration of BOD and COD of domestic wastewater. The method used is based  on  laboratory  analysis  of  BOD  and  COD  concentration  in  wastewater  samples.  The  process was  performed  under  a  batch  system  by  varying  the  concentration  of  waste  (20%,  25%,  33%  and 50%)  and  residence  time  in  reactor  (0,5,10,15,20)  days.  The  result  of  such  treatment  from  day  0  to day 20, there is the highest efficiency in treatment for BOD 78.26% at concentrations of 50% and the COD is 71.15% at a concentration of 20%.